IoT Based Smart Agriculture with Automatic Irrigation System with ESP8266 - et. al., Sudharshan K.M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Agriculture assumes an indispensable part in the improvement of horticultural nations. A rare subjects about agricultural have been frequently debasement the upgrading of the nation. Subsequently, the only response for this problem is keep agricultural by improving the present conformist policies for agriculture. Thus the approach is creation agriculture sharp operating mechanization and IoT innovations. Web of Things (IoT) empowers different uses of harvest development observing and choice, programmed water system choice help, and so on we proposed ESP8266 IoT Automatic water system framework to modernize and improve the profitability of the yield. This post discloses how to make IoT Smart Agriculture with Automatic Irrigation System utilizing some basic sensors that are accessible on the lookout. will utilize Capacitive Soil Moisture Sensor to quantify dampness content present in the dirt. Also to gauge Air Temperature and Humidity, lean toward DHT11 Humidity Temperature Sensor. Utilizing a 5V Power transfer we will control the Water Pump. At whatever point the sensor recognizes a low amount of dampness in the dirt, the engine turns on consequently. Subsequently, will consequently flood the field. When the dirt becomes wet, the engine kills. You can screen such an excess of happening distantly by means of Thingspeak Server online from any piece of the world